Resveratrol Supplementation Did Not Improve Cognition in Patients with Schizophrenia: Results from a Randomized Clinical Trial - Zortea, Karine; Franco, Viviane C.; Guimarães, Paula; Belmonte-de-Abreu, Paulo S. (Frontiers in Psychiatry, 2016)
Background Schizophrenia (SZ) is associated with psychotic experiences and cognitive deficits. Therefore, cognitive function is one of the most critical determinants of quality of life in this pathology. Resveratrol has been related to neuroprotective action, but there are no studies evaluating resveratrol in SZ. The objective of this study was to determine the efficacy of resveratrol supplementation on cognition in individuals with SZ. Methods This is a 1-month randomized, double-blind, and controlled trial (NCT 02062190), in which 19 men with diagnosis of SZ, aged 18–65 years, were assigned to a resveratrol supplementation group (200 mg) or placebo group (200 mg), with a 1-month follow-up. Applying a series of cognitive tests assessed neuropsychology performance (Hopkins Verbal Learning Test, Stroop Color and Word Test, and Weschler Adult Intelligence Scale) and Brief Psychiatric Rating Scale assessed psychopathology severity. Results There were no significant improvement in neuropsychology performance (episodic memory, working memory, attention and concentration capacity, inhibitory control, interference measures, selective attention, and mental flexibility) and psychopathology severity after 1 month of resveratrol supplementation (P > 0.05). Conclusion In conclusion, we have shown that 1 month of a resveratrol supplementation (200 mg/day) did not improve episodic memory, working memory, attention and concentration capacity, inhibitory control, interference measures, selective attention, and mental flexibility as compared with placebo in patients with SZ.